Reconstruction of Congenital Cranial Defect Using Autologous Bone Graft in Aplasia Cutis Congenita. Issue 3 (May 2020) - Seo, Du-Heon; Roh, Si-Gyun; Koh, Eun-Jeong; Shin, Jin Yong; Chang, Suk Choo; Lee, Nae-Ho
Abstract : Abstract: Many methods have been devised to repair cranial defects. Here, we report the use of a simple technique for the repair of a congenital cranial defect associated with aplasia cutis congenita (ACC). A newborn baby at 39 weeks of gestation was consulted with a scalp and cranial defect at the vertex measuring 3 × 1.5 cm. A 3-D CT scan of the skull confirmed the presence of a cranial defect at the sagittal suture and a normal brain structure. On the 13 th day of life, the newborn was taken to an operating room. An autologous bone graft was harvested from adjacent normal parietal bone and grafted into the debrided congenital cranial defect. The soft tissue defect was then covered by rotation flaps. The postoperative 3-D CT scan presented a well-positioned autologous bone graft. At 1 month postoperatively, the skull contour was normal and there was no palpable defect. We report a successful surgical outcome for a congenital cranial and soft tissue defect in ACC treated using an autologous bone graft and rotation flaps. Although conservative therapy may be an alternative option, we recommend appropriate surgical reconstruction in patients at risk of potentially fatal complications.